1993
DOI: 10.3109/10611869308996094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bile Acid Transporter in Enhancing Intestinal Permeability to Renin-Inhibitory Peptides

Abstract: To evaluate the bile acid transporter as a means of enhancing the ability of renin-inhibitory peptides (RIPs) to penetrate the intestinal mucosa, two RIP-cholic acid conjugates and an RIP-taurocholic acid conjugate were synthesized. Conjugation was through the N-terminus of an RIP and the 3-position of the bile acid, via a six-carbon spacer. An RIP derivative containing the spacer without the bile acid moiety was also synthesized. The bile acid-RIP conjugates and the RIP derivative were shown to be potent inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Although some reports have suggested involvement of these mechanisms in the transport of glycosylated macromolecules (12,23), no improved absorption was observed for glycosylated Lyz derivatives. Kim et al (19) reported that bile acid-conjugated small peptides could bind to intestinal bile acid transporters without being transported.…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports have suggested involvement of these mechanisms in the transport of glycosylated macromolecules (12,23), no improved absorption was observed for glycosylated Lyz derivatives. Kim et al (19) reported that bile acid-conjugated small peptides could bind to intestinal bile acid transporters without being transported.…”
Section: Discussionmentioning
confidence: 99%
“…These studies prove that the coupling of drug entities to bile acids does not cause a loss of affinity for the hepatic bile acid carrier. Apart from the necessity of a negatively charged group around the C-24 position, Kim et al [165] have shown that some size restrictions apply when compounds are coupled to the C-3 position. Both the 3 and the 24 positions appear to be usable coupling points for a prodrug stratagem.…”
Section: Liver and Gallbladder Deliverymentioning
confidence: 99%
“…161 Then, Ron's laboratory and collaborators at The Upjohn Company (Kalamazoo, MI) used the Caco-2 cell model to evaluate whether the bile acid transporter can enhance the ability of renin-inhibitory peptides to penetrate the intestinal mucosa by synthesizing and testing peptide-cholic acid conjugates. 162 A similar "one-two punch" was used by exploiting the functional expression of a biotin (vitamin H) transporter, now known to be the sodium-dependent multivitamin transporter (SMVT or SLC5A6), in Caco-2 cells and the intestine to assess whether oral absorption of peptidic HIV-1 protease inhibitors could be enhanced through biotin-peptide conjugation. 163,164 Such studies led to many subsequent applications of the Caco-2 cell and BBMEC models in Ron's laboratory to elucidate the structural features of peptides and peptidomimetics influencing their ability to cross cell membranes.…”
Section: Practical Models For Biological Barriers To Drug Deliverymentioning
confidence: 99%